Spontaneous levitation of dropped nucleus on first post-operative day. (5th May 2017) - Naik, Mayuresh P; Sethi, Harindersingh; Mehta, Anuj; Bhalla, Abhinav; Saluja, Komal
A 60-year-old male patient presenting with gradual painless progressive diminution of vision was diagnosed with nuclear sclerosis grade III (LOCS). Intra-operatively, there was a nuclear drop into the vitreous cavity. The patient was left aphakic and was deferred for further vitreoretinal procedure the next day. On first post-op day, the nucleus fragment (of roughly the same size that had dropped into the vitreous) was seen in the anterior chamber. A gentle ultrasonography B-Scan done for posterior segment evaluation was anechoic. Incision was enlarged and viscoexpression of the nucleus fragment was done followed by thorough anterior vitrectomy. Post-operatively, dilated full fundus examination showed clear vitreous cavity without any evidence of retinal tear or detachment. This was later confirmed by an anechoic ultrasonography B-Scan. After 2 weeks, three-piece foldable IOL was placed in the sulcus with posterior optic capture and the patient attained a best-corrected visual acuity of 6/9P.